ASPEK PERJANJIAN ELECTRONIC COMMERCE DAN IMPLIKASINYA PADA HUKUM PEMBUKTIAN DI INDONESIA - C. Maya Indah (Faculty of Law, Universitas Diponegoro, 2010)
The problem of law in cyber activities is implementation of law evidence. Including the problem are authenticity of law subject in making transaction by cyber, commitment ofpacta sun servanda principle, transfer of right mechanism, accountability of each party, electronic document legality, and digital signature as a tool of evidence, resolution of conflict, and jurisdiction in private law cases. The problem in E-commerce contract is legality of standard contract in E-commerce. It is important in Law Private perspective about lisenceof data ownership, and authenticity of each party in trading bycyberspace.